Psychological impact of comprehensive tumor genomic profiling results for advanced cancer patients. Issue 7 (July 2022) - Butow, Phyllis N.; Best, Megan C.; Davies, Grace; Schlub, Timothy; Napier, Christine E.; Bartley, Nicci; Ballinger, Mandy L.; Juraskova, Ilona; Meiser, Bettina; Goldstein, David; Biesecker, Barbara; Thomas, David M.; et al.
Abstract: Objective: Comprehensive tumor genomic profiling (CTGP) is increasingly used to personalize treatments, providing hope, but potentially disappointment, for patients. We explored psychological outcomes in patients with advanced, incurable cancer, after receiving CTGP results. Methods: Participants with advanced, incurable cancer (n = 560, mean age 56, 43% university educated) in this longitudinal substudy of the Molecular Screening and Therapeutics Program (MoST), completed questionnaires before and after receiving CGP results. MoST participants, recruited from Australian oncology clinics, undergo CTGP, and if there are actionable findings, are offered treatment in a related therapeutic trial if available. Results: Patients who received actionable results, (n = 356, 64%) had lower gene-related distress (MICRA) ( p  < 0.001) and Impact of Events scores ( p  = 0.039) than patients with non-actionable results. Those with actionable results offered ensured access to tailored treatment (n = 151) reported lower anxiety ( p  = 0.002) and depressive symptoms ( p  = 0.01) and greater hope ( p  = 0.002) than those not offered. Positive attitudes towards uncertainty and higher self-efficacy for coping with results were associated with lower psychological distress and uncertainty, and higher hope and satisfaction with the decision to have CTGP ( ps =0.001–0.047). Those with higher knowledge reported greater anxiety ( p  = 0.034). Conclusion: Receiving a non-actionable CTGP result, or an actionable result without ensured access to treatment, may cause increased distress in advanced cancer patients. Coping style was also associated with distress. Practice implications: Pre-testing assessment and counseling addressing attitudes toward uncertainty and self-efficacy, and post-CTGP result support for patients receiving a non-actionable result or who receive an actionable results without ensured access to treatment, may benefit patients. Highlights: Actionable results and direct access to tailored treatment were associated with reduced distress in advanced cancer patients. Positive attitudes towards uncertainty and higher self-efficacy was associated with lower levels of psychological distress. Some patients who do not receive results leading to tailored treatment may benefit from support and counseling at this time. Addressing attitudes toward uncertainty and self-efficacy may assist patients to cope with results.